Pivotal response treatment for autism: A brief report on training for rural communities. Issue 7 (18th March 2021) - Dahiya, Angela V.; Openden, Daniel; Ostmeyer, Katrina F.; Anderson, Rachel M.; Scarpa, Angela
Abstract: Many providers from rural communities feel ill‐prepared to treat children with autism spectrum disorder (ASD). Cost‐effective training in Pivotal Response Treatment (PRT), an evidence‐based ASD treatment, can address unmet needs for rural communities. The current study examined a 1‐day general PRT workshop for parents and professionals followed by a 3‐day small, intensive training for professionals. Fifty‐two parents and providers completed surveys before and after Day 1, indicating improvements in perceived stress and confidence. Three providers were trained during Days 2–4, and submitted four 10‐min videos (i.e., baseline, 1‐week, 1‐month, and 2‐months post‐training) working with a target child discussed in the training and another child. Videos were coded for correct PRT implementation and analyzed using a single‐subject A–B design with generalization and maintenance probes. All providers learned to apply PRT techniques with the target child and generalized skills to another child within 1‐week post‐training, with partial maintenance. Implications for rural mental health training in evidence‐based practices are discussed.